Electronic Structural Analysis of Copper(II)-TEMPO/ABNO Complexes Provides Evidence for Copper(I)-Oxoammonium Character - Walroth, Richard C; Miles, Kelsey C; Lukens, James T; MacMillan, Samantha N; Stahl, Shannon S; Lancaster, Kyle M (Journal of the American Chemical Society, 2017)
Copper/aminoxyl species are proposed as key intermediates in aerobic alcohol oxidation. Several possible electronic structural descriptions of these species are possible, and the present study probes this issue by examining four crystallographically characterized Cu/aminoxyl halide complexes by Cu K-edge, Cu L -edge, and Cl K-edge X-ray absorption spectroscopy. The mixing coefficients between Cu, aminoxyl, and halide orbitals are determined via these techniques with support from density functional theory. The emergent electronic structure picture reveals that Cu coordination confers appreciable oxoammonium character to the aminoxyl ligand. The computational methodology is extended to one of the putative intermediates invoked in catalytic Cu/aminoxyl-driven alcohol oxidation reactions, with similar findings. Collectively, the results have important implications for the mechanism of alcohol oxidation and the underlying basis for cooperativity in this co-catalyst system.